Public administration research in Taiwan: A content analysis of journal articles (1990-2010) - Sun, Milan Tung-Wen; Lin, Jessica Yu-Wen (2014)
This article presents a description of the discipline of public administration in Taiwan and a survey of research on the subject. A total of 1,090 articles appearing in five public administration journals during the period of 1990 to 2010 were examined from three aspects: authorship and productivity, research subject and keyword, and research purpose and method. Comparisons were made across time (1990-1999, 2000-2010) and by type of journal (TSSCI and Non-TSSCI). Research findings indicate that, in Taiwan, the focus of public administration research has been on such topics as public policy, new public management (NPM), public organization management, and intergovernmental relations. The style of scholarship is typically not empirical, though there is evidence of change here over time. In a broader perspective, public administration research has been conducted in an increasingly very competitive circumstance. It is argued that there will be ample opportunity for dialogue between scholars of public administration in Taiwan and the international community in the field. - Reproduced.
Keywords: Research; Public administration